Assessing Smallholder Farmer's Participation in the Wheat Value Chain in North-West Mt. Kenya - Mwangi, Veronica; Owuor, Samuel; Kiteme, Boniface; Giger, Markus (Frontiers in Sustainable Food Systems, 2021)
Wheat is the second most important carbohydrate staple in Kenya and is produced by both smallholder and large-scale farmers. Smallholders are the majority, but produce <20% of the total national production. Compared to large-scale farmers, they have been considered to be less efficient producers and thus fail to benefit fully from their participation in the wheat value chain. This study aims at establishing the value accruing to smallholder and large-scale farmers participating in wheat production in north-west Mt. Kenya. For comparative purposes and to explore the potential of smallholder farmers, a sample of 58 smallholder and seven large-scale farmers was selected for the study. We use budget analysis to determine the gross output, cost of production and gross margins attained by the smallholder and large-scale farmers. Further, an analysis of constraints to productivity is done to establish the factors hindering farmers from reaching high yield potential. Results of the study show that smallholder farmers obtain lower yields, have higher costs of production per bag of wheat and lower gross margins compared to large-scale farmers. High cost of inputs, low market prices, low bargaining power, high cost of machinery services, diseases and weeds were among factors excluding smallholder farmers from benefitting from their participation in the value chain. However, results also show that smallholder farmers can produce wheat profitably albeit with necessary support. Thus, interventions should consider these constraints and aim at improving smallholder farmers' horizontal and vertical integration in the value chain. We recommend continued investment in research and development on wheat, adoption of climate resilient agricultural practices, improvements in the fertilizer subsidy programme and creating or increasing participation in producer groups that will provide possibilities of increased bargaining power and reduction of costs through improved access to machinery services, markets and credit.